Introductory Statistics / Fifth Edition - Wonnacott Ronald J; Wonnacott Thomas H (John Wiley & Sons, 1990)
Basic Probability and Statistics, The Nature of Statistics, Descriptive Statistics, Probability, Probability Distributions, Two Random Variables, Inference for Means and Proportions, Sampling, Point Estimation, Confidence Intervals, Hypothesis Testing, Analysis of Variance (ANOVA), Regression: Relating Two or More Variables, Fitting a Line, Simple Regression, Multiple Regression, Regression Extensions, Correlation, Topics in Classical and Bayesian Inference, Nonparametric and Robust Statistics, Chi-Square Tests, Maximum Likehood Estimation, Bayesian Inference, Bayesian Decision Theory, Appendixes, Tables, References, Index.